Bis(μ2-N-methyl-N-phenyldithiocarbamato)-κ3S,S′:S;κ3S:S,S′-bis[(N-methyl-N-phenyldithiocarbamato-κ2S,S′)cadmium]: crystal structure and Hirshfeld surface analysis - Suwardi, S.A.N.; Lee, S.M.; Lo, K.M.; Jotani, M.M.; Tiekink, E.R.T. (International Union of Crystallography, 2017)
The title compound, [Cd2(C8H8NS2)4], is a centrosymmetric dimer with both chelating and μ2-tridentate di-thio-carbamate ligands. The resulting S5 donor set defines a CdII coordination geometry inter-mediate between square-pyramidal and trigonal-bipyramidal, but tending towards the former. The packing features C - H...S and C - H...π inter-actions, which generate a three-dimensional network. The influence of these inter-actions, along with intra-dimer π-π inter-actions between chelate rings, has been investigated by an analysis of the Hirshfeld surface.